2017
DOI: 10.1212/wnl.0000000000004669
|View full text |Cite|
|
Sign up to set email alerts
|

Multiparametric MRI changes persist beyond recovery in concussed adolescent hockey players

Abstract: Objective:To determine whether multiparametric MRI data can provide insight into the acute and long-lasting neuronal sequelae after a concussion in adolescent athletes.Methods:Players were recruited from Bantam hockey leagues in which body checking is first introduced (male, age 11–14 years). Clinical measures, diffusion metrics, resting-state network and region-to-region functional connectivity patterns, and magnetic resonance spectroscopy absolute metabolite concentrations were analyzed from an independent, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
86
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 83 publications
(95 citation statements)
references
References 38 publications
4
86
0
Order By: Relevance
“…The decrease in Gln and Gln/ Cr observed in the days and months post-concussion in the current study is consistent with studies of rodent models using Carbon-13 spectroscopy that have found reduced Gln labeling up to 24-hr postinjury (Bartnik, Lee, Hovda, & Sutton, 2007). A previous cross-sectional study of 13-14 year old hockey players using the same methodology as the current study also found a statistical trend toward reduced glutamine levels in the concussed athletes three months after concussion (Manning et al, 2017). Since Gln is a by-product of glucose metabolism these results suggest that the reduction in Gln may be the result of reduced glucose metabolism (Bartnik et al, 2007).…”
Section: Reduced Glutamine and Gln/crsupporting
confidence: 91%
“…The decrease in Gln and Gln/ Cr observed in the days and months post-concussion in the current study is consistent with studies of rodent models using Carbon-13 spectroscopy that have found reduced Gln labeling up to 24-hr postinjury (Bartnik, Lee, Hovda, & Sutton, 2007). A previous cross-sectional study of 13-14 year old hockey players using the same methodology as the current study also found a statistical trend toward reduced glutamine levels in the concussed athletes three months after concussion (Manning et al, 2017). Since Gln is a by-product of glucose metabolism these results suggest that the reduction in Gln may be the result of reduced glucose metabolism (Bartnik et al, 2007).…”
Section: Reduced Glutamine and Gln/crsupporting
confidence: 91%
“…Whether hyperconnectivity is adaptive or maladaptive is difficult to establish, as the relationship between hyperconnectivity and clinical measures has varied across studies of mTBI. Some have associated hyperconnectivity with less severe injury (Manning et al, ; Yan et al, ). Others have reported hyperconnectivity associated with more symptoms or longer recovery time, consistent with current findings (Churchill, Hutchison, Richards, et al, ; van der Horn et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, our observation of similar time course of recovery for physiological effects and clinical symptoms following SRC runs contrary to recent work suggesting physiological effects extend beyond clinical recovery. For example, group differences in rs-FC have been reported in clinically recovered athletes after clearance for complete RTP (Churchill, Hutchison, Richards, et al, 2017), at approximately 10 days postinjury (Johnson et al, 2012), after 3 months postconcussion (Manning et al, 2017), and even within 6 months postconcussion (Czerniak et al, 2015). As highlighted in a recent systematic review, much of the prior work has included single postinjury visits and/or has included relatively small numbers of injured athletes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 In humans, however, direct cellular and metabolic monitoring has occurred primarily in the ICU settings for more severe brain injuries. 37 At this stage, none of these acute or sustained changes have been specifically correlated with headache in a manner that could guide therapeutic intervention. 36 Imaging and serum biomarkers confirm that metabolic and cerebral blood flow derangements typically last up to 30 days post injury.…”
Section: Basic Mechanisms Of Pth As Targets For Therapymentioning
confidence: 99%